Japan in the 21st Century : Environment, economy, and society - Karan, Pradyumna P. (University Press of Kentucky, 2005)
This book provides a comprehensive survey of Japan's environment, society, and economy in the twenty-first century. Karan examines challenges such as demographic change, urbanization, environmental constraints, economic restructuring, and policy responses. Field reports, maps, and case studies enrich the narrative.